The Effect of Environmental Performance and Environmental Costs on Firm Value with Profitability as a Mediating Variable - Rinaldi Kartobi; Fajar Gustiawaty Dewi (Studi Akuntansi dan Bisnis Indonesia, 2025)
Purpose: This study examines the effect of environmental performance and environmental costs on firm value with profitability as a mediating variable in energy sector companies listed on the Indonesia Stock Exchange during 2022–2024. Methodology/approach: Using a quantitative approach, 75 firm-year observations are selected through purposive sampling from annual and sustainability reports. Firm value is proxied by Tobin’s Q, profitability by ROA, and environmental variables by disclosure indices. Data are analyzed using multiple regression, path analysis, and the Sobel test. Results/findings: Environmental performance negatively affects profitability, while environmental costs have no significant effect. Both variables do not directly influence firm value. Profitability positively affects firm value and mediates the effect of environmental performance, but not environmental costs. Conclusions: The capital market in the Indonesian energy sector remains more financially oriented than environmentally oriented in determining firm value. Limitations: The study focuses only on the energy sector and a short observation period. Contribution: This study enriches empirical evidence on sustainability and firm value relationships in emerging markets.